The training market in 2024 : analyses based on the BIBB survey of newly concluded training contracts and the training market statistics of the Federal Employment Agency as of 30 September - Weller, Sabrina Inez [Verfasser]; Christ, Alexander [Verfasser]; Milde, Bettina [Verfasser]; Granath, Ralf-Olaf [Verfasser] (Bundesinstitut für Berufsbildung, 2026)
"After the training market slowly recovered from the losses caused by the coronavirus pandemic in recent years and slight growth was recorded again, the number of newly concluded training contracts in 2024 fell by 0.5 per cent compared to the previous year to around 486,700 contracts. This is one of the key fi ndings of the BIBB’s analyses of the development of the training market in 2024. It is based on the BIBB survey of newly concluded training contracts as of 30 September and on the training market statistics of the Federal Employment Agency. The publication provides an overview of unsuccessful market entries and matching problems, as well as the supply of and demand for training places." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; 370; Ausbildungsstellenmarkt; Ausbildungsstellenbilanz; Ausbildungsplatzangebot; Ausbildungsplatznachfrage; Angebot-Nachfrage-Relation; Unbesetzte Ausbildungsplätze; Mismatch; Ausbildungsbeteiligung; Quantitative Angaben; 2024